Membangun Mail Server Berbasis Linux Menggunakan Postfix dan Dovecot - Sirajuddin Hawari; Abdullah Ammar; Ahmad Nur Ihsan Purwanto; Aaqila Dhiyaanisafa Goenawan (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2022)
In today's era, information exchange is fast and can be done in various ways and one of them is using email. There are many free email service providers that can be used, such as Gmail, Yahoo Mail and Outlook. In addition to free services, email servers can also be used to serve communication between clients and transfer data over the local network using a custom domain for the company. The purpose of this report is to build your own email server using the server development method using the Linux Ubuntu 18.04 operating system and the software Postfix and Dovecot as its supports. The results of this mail server work can send emails from one user to another through the terminal directly correctly. Sending can be done directly using the terminal without creating a text first or creating a text before sending it. Both ways are equally successful in the main process in the mail server.